Effects of Celebrity Characteristics, Perceived Homophily, and Reverence on Consumer-Celebrity Para-Social Interaction and Brand Attitude - Zhang, Ke; Zhang, Menghan; Li, Chao (Frontiers in Psychology, 2021)
This research explored how perceived homophily and reverence of consumers bridge the gap between endorser characteristics and consumer-celebrity para-social interaction (PSI). Online surveys were utilized to collect data from consumers. The results based on structural equation modeling showed that the perceived attractiveness and expertise of a celebrity were separately antecedent to the perceived homophily and reverence of consumers for the celebrity. This in turn allowed consumers to build PSI with the celebrity and led to a positive attitude toward the celebrity-endorsed brand. No differences were found between non-fans and fans of the selected celebrity regarding the confirmed path from celebrity characteristics to consumer brand attitude via PSI and its influencing factors. This work highlighted the significance of consumer-celebrity relations for endorsement effectiveness through proving consumer-celebrity PSI and its drivers as indispensable steps in the endorsement process.